Chambly Mills, 1784‑1815 - Noël, Françoise (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1985)
AbstractThe study of Gabriel Christie's investments in, and operation of, Chambly Mills in the late eighteenth century provides insight into the role of a small-scale seigneurial enterprise in the rural economy. Despite the sizable investment involved, the flour mill employed only a small number of permanent wage workers, and other cash expen- ditures were minimal. The mill can therefore be seen to have operated within a traditional structure of rural society rather than as a force for change. The mill, however, also depended on artisanal labour and a link between the establishment of the mills and the growth of the village is suggested. Seigneurial investment may have been a major factor in the increasing number of villages in Lower Canada between 1815 and 1831. A need for further study of the role of seigneurial capital in the wider economy is indicated, an area which the focus on centralized and large-scale industries has left virtually unexplored.